Herbicides versus Nitrogen Cycle: Assessing the Trade-Offs for Soil Integrity and Crop Yield—An In-Depth Systematic Review - Brochado, Maura Gabriela da Silva; Silva, Laryssa Barbosa Xavier da; Lima, Alessandro da Costa; Guidi, Yure Marin; Mendes, Kassio Ferreira (Nitrogen (Basel, Switzerland), 2023)
The interaction of herbicides in the nitrogen cycle and their consequences on soil health and agricultural production are essential topics in agronomic research. In this systematic review article, we have synthesized recent studies on this subject. The results revealed that the indiscriminate use of herbicides can have negative effects on vital processes in the nitrogen cycle, such as reduced enzymatic activity and microbial respiration. Moreover, herbicides alter the soil microbial composition, affecting nitrogen cycling-related activities. Symbiotic nitrogen fixation is also impaired, resulting in a reduction in the population of nitrogen-fixing bacteria and a decrease in the availability of this nutrient in the soil. These effects compromise soil fertility and the release of nitrogen to plants. Therefore, sustainable agricultural practices must be adopted, considering nitrogen cycling efficiency and the preservation of soil and natural resources. This understanding is crucial for guiding appropriate management strategies aimed at minimizing the negative effects of herbicides on the nitrogen cycle and ensuring soil health and agricultural productivity.